Study of Spin–Spin Correlations between Quark and a Spin-1/2 Composite System - Satvir Kaur; Harleen Dahiya (Advances in High Energy Physics)
We study the correlation between the fermion composite system and quark spins by using the light-cone quark–diquark model. We do the calculations for u-quark and d-quark in the fermion system by considering different polarization configurations of both. The contribution from scalar and axial-vector diquarks is taken into account. The overlap representation of light-front wavefunctions is used for the calculations. The spin–spin correlations for u and d quarks are presented in transverse impact-parameter plane and transverse momentum plane as well.